2015
DOI: 10.1111/coa.12443
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative complications after total laryngectomy following radiotherapy or chemoradiation: a 10‐year retrospective longitudinal study in Eastern Denmark

Abstract: The frequencies of postoperative complications after total laryngectomy were comparable with similar international studies, although fistula formation rate is increasing in Denmark. We suggest optimising treatment of COPD and to further encourage to smoking cessation. We propose that development of fistulas >2 months after surgery prompts immediate biopsies. Additionally, we suggest standardised registration of surgical techniques to identify variables affecting the frequency of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…Wound complications (specifically PCFs) and hematomas are well recognized as the most common complications in primary and salvage TL . This study found a strong association between wound complications and both current and former smokers, and its findings support prior evidence linking smoking to overall complications and PCFs in TL . Despite the clinically apparent negative impact of smoking on wound healing, a recent systematic analysis of smoking and perioperative complications in head and neck cancer found mixed results, largely because of the heterogeneity of the studies in terms of methodology, smoking classification, and outcomes of interest.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Wound complications (specifically PCFs) and hematomas are well recognized as the most common complications in primary and salvage TL . This study found a strong association between wound complications and both current and former smokers, and its findings support prior evidence linking smoking to overall complications and PCFs in TL . Despite the clinically apparent negative impact of smoking on wound healing, a recent systematic analysis of smoking and perioperative complications in head and neck cancer found mixed results, largely because of the heterogeneity of the studies in terms of methodology, smoking classification, and outcomes of interest.…”
Section: Discussionsupporting
confidence: 70%
“…[16][17][18] This study found a strong association between wound complications and both current and former smokers, and its findings support prior evidence linking smoking to overall complications and PCFs in TL. 19 Despite the clinically apparent negative impact of smoking on wound healing, a recent systematic analysis of smoking and perioperative complications in head and neck cancer found mixed results, largely because of the heterogeneity of the studies in terms of methodology, smoking classification, and outcomes of interest. Nevertheless, this association is supported by strong physiologic plausibility and evidence of relative tissue hypoxemia in current and/or recent smokers as well as knowledge of common comorbidities among smokers that negatively affect wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that preoperative current smoking, chronic obstructive pulmonary disease, tumour localisation in the hypopharynx and residual or recurrent tumour following surgery are factors associated with complications after salvage TL …”
mentioning
confidence: 99%
“…We have previously demonstrated that preoperative current smoking, chronic obstructive pulmonary disease, tumour localisation in the hypopharynx and residual or recurrent tumour following surgery are factors associated with complications after salvage TL. 7 Only a few studies have investigated the prognostic factors for survival following salvage TL, and this study represents one of the largest from a single institution.…”
mentioning
confidence: 99%
“…Although there may be some debate regarding the optimal treatment for locally advanced laryngeal cancer, there is agreement that comorbidities play an important role in guiding treatment decisions and outcomes. Multiple studies have demonstrated that the primary predictor of complications after a TL is a salvage setting after RT or CRT failure . Several large database reviews have more recently identified specific comorbidities that are associated with increased complications or readmissions after a TL .…”
Section: Discussionmentioning
confidence: 99%